Simulating crude oil exposure, uptake and effects in North Atlantic Calanus finmarchicus populations. (December 2020) - Broch, Ole Jacob; Nepstad, Raymond; Ellingsen, Ingrid; Bast, Radovan; Skeie, Geir Morten; Carroll, JoLynn
Abstract: A simulation model framework (SYMBIOSES) that includes a 3-dimensional ocean physics and biology model and a model for transport and fate of oil was used to investigate the potential for bioaccumulation and lethal/sublethal effects of oil components in the copepod Calanus finmarchicus in the Lofoten–Vesterålen archipelago of Norway. The oil model is coupled with the biology model by way of a bioaccumulation model, from which mortality and reduction in reproduction are calculated via a total body burden (TBB). The simulation results indicate that copepod body burden levels are affected by the spill type (surface spill, subsea blowout) and the spill timing (spring, autumn). The effects of oil component bioaccumulation on the copepod population for all scenarios are small, though greatest in the subsea blowout scenarios. We attribute this to the limited spatial and temporal overlap between copepods and oil in the environment simulated by the model. The coupling of the processes of oil transport, bioaccumulation/excretion and the associated effects are discussed in the context of the model framework and with a view towards applications for Ecological Risk Assessment (ERA). Highlights: Oil bioaccumulation in Calanus is highest for subsea blowout spills. Oil releases are confined to the shelf by currents, resulting in higher bioaccumulation by Calanus on the shelf. Lethal/sub lethal effects at the population level are minor for all scenarios. Effects are minor due to limited overlap of oil in space and time with Calanus .